Groin Pain Syndrome Italian Consensus Conference on terminology, clinical evaluation and imaging assessment in groin pain in athlete. Issue 1 (29th November 2016) - Bisciotti, G N; Volpi, P; Zini, R; Auci, A; Aprato, A; Belli, A; Bellistri, G; Benelli, P; Bona, S; Bonaiuti, D; Carimati, G; Canata, G L; et al.
Abstract : The nomenclature and the lack of consensus of clinical evaluation and imaging assessment in groin pain generate significant confusion in this field. The Groin Pain Syndrome Italian Consensus Conference has been organised in order to prepare a consensus document regarding taxonomy, clinical evaluation and imaging assessment for groin pain. A 1-day Consensus Conference was organised on 5 February 2016, in Milan (Italy). 41 Italian experts with different backgrounds participated in the discussion. A consensus document previously drafted was discussed, eventually modified, and finally approved by all members of the Consensus Conference. Unanimous consensus was reached concerning: (1) taxonomy (2) clinical evaluation and (3) imaging assessment. The synthesis of these 3 points is included in this paper. The Groin Pain Syndrome Italian Consensus Conference reached a consensus on three main points concerning the groin pain syndrome assessment, in an attempt to clarify this challenging medical problem.